2008
DOI: 10.1590/s0004-282x2008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term facial nerve clinical evaluation following vestibular schwannoma surgery

Abstract: -Background: Facial function is important in accompaniment of patients operated on vestibular schwannoma (VS). Objetive: To evaluate long term facial nerve function in patients undergoing VS resection and to correlate tumor size and facial function in a long-term follow-up. Method: Transversal study of 20 patients with VS operated by the retrosigmoid approach. House-Brackmann Scale was used preoperatively, immediately after surgery and in a long-term follow-up. Student t test was applied for statistic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
(66 reference statements)
2
19
0
3
Order By: Relevance
“…The facial nerve can usually tolerate a large degree of stretching, compression or distortion without apparent facial palsy [19, 24]. However, as the tumor grows, the nerve comes under even greater tension, which increases the likelihood of stretch injury, and this may explain the high rate of facial palsy seen in patients with large tumors [19, 24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The facial nerve can usually tolerate a large degree of stretching, compression or distortion without apparent facial palsy [19, 24]. However, as the tumor grows, the nerve comes under even greater tension, which increases the likelihood of stretch injury, and this may explain the high rate of facial palsy seen in patients with large tumors [19, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Even though advances in surgical techniques have improved facial nerve outcomes, functional preservation is still an issue because injury to the facial nerve has significant physical and psychological consequences for the patient [1416]. It has been suggested that age, tumor size, and surgical approach all can impact ultimate facial functional outcome [1619]. …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, according to other authors [20] the risk of facial palsy after vestibular schwannoma surgery is the lowest among all available surgical approaches when using the translabyrinthine approach. In order to assess the facial nerve function, pre-as well as post-operatively, the most commonly used tool was the House-Brackmann scale [4,7,8,13,16,17,21]. Facial electromyography (EMG) has also been a useful tool, because it facilitates the surgical procedure and plays an important role in the prevention of facial paresis.…”
Section: Facial Paresismentioning
confidence: 99%
“…A clinical trial involving facial nerve functionality preservation [21] tested the efficacy of one dose of corticosteroids (usually dexamethasone) intraoperatively. The theory was based on the fact that facial nerve malfunction can be a result of neural edema and that patients might benefit from corticosteroid use, as in idiopathic facial palsy.…”
Section: Facial Paresismentioning
confidence: 99%
“…Prognostic factors such as age, tumor size, extent of resection, and surgical approach have been implicated for predicting facial nerve function outcome after surgical removal of VS. 20,55,59,102 In a meta-analysis of 296 studies involving more than 25,000 patients that included outcome data for facial nerve function of surgically treated VS patients, Sughrue et al 86 found that tumor size of less than 20 mm, the use of the middle fossa approach, and the use of neuromonitoring during surgery were associated with facial nerve preservation. However, others have found through retrospective review of patients presenting at single institutions that for small tumors, specifically those smaller than 20 mm, the preservation of facial G-I).…”
Section: Prognosticators Of Facial Nerve Outcome After Vs Surgerymentioning
confidence: 99%